Untainted Desires: Analyzing Sexuality in The Phantom of the Opera through Freudian Lens: Keinginan yang Tidak Murni: Analisis Seksualitas dalam “The Phantom of the Opera” melalui Kacamata Freudian - Falcunit, Andrea Uella B.; Capitle , Riza Mae J.; Basiao, Micha Ylla D.; Ferrariz Jr., Genaro; Bonganciso, Ruel T.; Normandia, John Jonathan N. (Journal of Literature and Education, 2024)
The article’s purpose is to examine the prevalence of sexuality in Gaston Leroux’s The Phantom of the Opera by analyzing the impacts of the characters’ background/milieu on their sexuality, how sexuality is illustrated in The Phantom of the Opera, and how social and moral constructs influence the characters’ expression of sexuality. The researchers utilized Content Analysis and Psychodynamics. The results revealed that Christine’s excessive influence of male presence during childhood made her a masculine woman while Raoul’s excessive influence of female presence made him an effeminate man. Christine’s and Raoul’s respective traits balance each other; however, the existing social and moral constructs regulate their behaviors to express their sexualities. On the other hand, Erik’s lack  of masculine and feminine traits and key figures to follow hindered his development of morals and sexuality. Understanding the significance of the characters’ background and milieu in shaping their sexuality as illustrated in Gaston Leroux’s literary work urges readers and students to redefine the quality of the relationships they established.